Delivered by women, led by men: A gender and equity analysis of the global health and social workforce - World Health Organization (World Health Organization, 2019)
Demographic changes and rising health care demands are projected to drive the creation of 40 million new jobs by 2030 in the global health and social sector. In parallel, there is an estimated shortfall of 18 million health workers, primarily in low- and middle-income countries, required to achieve the Sustainable Development Goals (SDGs) and universal health coverage. The global mismatch between health worker supply and demand is both a cause for concern and a potential opportunity. Since women account for 70% of the health and social care workforce, gaps in health worker supply will not be closed without addressing the gender dynamics of the health and social workforce. The female health and social care workers who deliver the majority of care in all settings face barriers at work not faced by their male colleagues. This not only undermines their own well-being and livelihoods, it also constrains progress on gender equality and negatively impacts health systems and the delivery of quality care. In November 2017, the World Health Organization (WHO) established the Gender Equity Hub (GEH), co-chaired by WHO and Women in Global Health under the umbrella of the Global Health Workforce Network. The GEH brings together key stakeholders to strengthen gender-transformative policy guidance and implementation capacity for overcoming gender biases and inequalities in the global health and social workforce, in support of the implementation of the Global Strategy on Human Resources for Health: Workforce 2030, and the Working for Health five-year action plan (2017–2021) of WHO, the International Labour Organization (ILO) and the Organisation for Economic Co-operation and Development (OECD). In 2018, the GEH identified and reviewed over 170 studies in a literature review of gender and equity in the global health workforce, with a focus on four themes: occupational segregation; decent work free from bias, discrimination and harassment, including sexual harassment; gender pay gap; and gender parity in leadership. This report will inform the next phase of the work of the Global Health Workforce Network GEH, which seeks to use these research findings to advocate gender-transformative policy and action.
https://apps.who.int/iris/handle/10665/311322
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discours dominant; droits des femmes*; inégalités; inégalités salariales; projet charge mentale; périodes historiques; rapports sociaux de sexe; systèmes d'oppressions; thématiques; travail; travailleureuses de la santé